Social enterprise marketing: review of literature and future research agenda. Issue 1 (7th August 2019) - Bandyopadhyay, Chinmoy; Ray, Subhasis
Abstract : Purpose: The purpose of this paper is to review existing literature on marketing in social enterprises (SEs). It identifies major trends and issues and highlights gaps in the existing knowledge base on social enterprise marketing (SEM). Design/methodology/approach: Relevant articles on SEM were searched, following the PRISMA framework, in online databases using keywords and phrases like "marketing in social enterprises, " "marketing strategy/practice in social enterprises, " "social enterprise marketing" and "business practices in social enterprises." After screening and checking for eligibility, 47 significant articles published in 21 peer-reviewed journals during 1995–2018 were selected for review. Findings: The findings suggest that marketing in SEs has different issues and challenges when compared to marketing practices adopted by conventional business organizations. They are forced to address the varied expectations of the stakeholders in a resource-constrained situation, which creates problems for them. The review also highlights the fact that resource constraints, legacy mindset, and lack of marketing skills limit the impact of marketing practices in SEs. To address these issues, many social entrepreneurs survive through cost-effective marketing techniques. Originality/value: To the authors' knowledge, this is the first effort to identify and analyze extant literature in SEM. The resultant themes and research gaps highlight the current status of SEM literature. The paper can help SEs to understand and plan their marketing activities for better impact and profitability. Future research can draw on the findings of this review.